Development of a Compact, Reliable, and Electrostatically Actuated Device for Microfluidic-Based Active Glasses - Simon Kulifaj; Clément Chauvin; Antoine Bouvier; Solène Meinier; Fengzhi Gu; Jérôme Degouttes; Nicolas Terrier; Patrick Pittet; Bruno Berge (Proceedings)
We present the development study of a reliable and low-power actuator for microfluidics-based active glasses. The adaptive part of the lens implements two liquids of a specific refractive index separated by a thin membrane, the modification of their relative volumes allowing adaptive optical power corrections. The proposed actuator is connected to an adaptive lens by microchannels since it is intended to be installed in the temple of the glasses. The actuation is based on the electrostatic displacement of a thin film, which changes the relative volumes of two cavities filled with these liquids. The metalized film is placed slack with an “S-shape” between two electrodes biased with the actuation voltage. Very compact actuator prototypes have been developed and characterized. Power corrections ranging from +0D to +3D can be achieved via liquid volume displacement as low as 120 µL and with a power consumption of a few mW. The prototypes show good reliability without any significant change in their operation after more than 1 million actuations. For RD purposes, we have replaced some electrodes with transparent windows. With this setup, we show experimental results on the interplay between the performances and the film folding inside the actuator.